A milk transportation problem with milk collection centers and vehicle routing. (March 2022) - Paredes-Belmar, Germán; Montero, Elizabeth; Leonardini, Omar
Abstract: In this work, we study, model, and propose two approaches to solve a raw milk transportation problem inspired by a real case of a milk company in Chile. The milk is produced by a set of farms scattered in a large rural area. The company must collect all the production daily using a truck fleet. We address the location of milk collection centers to reduce transportation costs. Each center has a limited capacity and a reduced truck fleet, composed of small trucks, to collect a substantial proportion of the produced milk. Once the milk is accumulated in the collection centers, a fleet of big trucks, traveling from a processing plant, collects the milk of each collection center and some large farms. We propose a mixed-integer linear programming model, a three-stage approach based on mathematical models, and an iterated local search approach to face this problem. We evaluate these approaches' performance using a small case and several real-world examples, including a clustering approach to divide the instance into small sub-instances. The results obtained for the real-world instance show improvements of up to 10% percent when milk collection centers are allowed. Graphical abstract: Highlights: We introduce a novel milk collection problem, inspired by current practice: A milk transportation problem with milk collection centers and vehicle routing. We locate a set of milk collection centers in the milk collection network, using different truck fleets for milk collection. We solve the problem optimally for test instances, using an mixed linear integer programming model, and heuristically in a real case. The milk collection centers reduce the transportation costs by up to 10%.